Adolescence in times of social-ecological crisis. Perspectives for social pedagogical analysis and research - Marie Frühauf (Social Work and Society)
Against the background of current multiple crises, above all the social-ecological crisis, the question arises how the phase of adolescence and its arrangement in fields of social pedagogy/social work are affected by this. Quantitative research shows that many young people are worried about the future because of the climate crisis. These surveys also show that the experience of the crisis is embedded in class and gender relations. However, there is a lack of qualitative research on this issue in general and on social pedagogical responses in particular. This article develops a perspective for social pedagogical research that focuses on both the affective and the social dimensions of adolescence. On this basis, initial reflections are made on the significance of the social-ecological crisis for negotiating adolescence between professionals and adolescents in the field of Open Child and Youth Work.